2023
DOI: 10.3390/app132011385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rock Dissolution on Two-Phase Relative Permeabilities: Pore-Scale Simulations Based on Experimental Data

Darezhat A. Bolysbek,
Alibek B. Kuljabekov,
Kenbai Sh Uzbekaliyev
et al.

Abstract: Relative phase permeability is an important characteristic of multiphase flow in porous media. Its assessment is an urgent issue when the pore structure changes due to rock dissolution. This article examines the effect of carbonate rock dissolution on two-phase flow based on images obtained by X-ray microcomputed tomography with a spatial resolution of ~18 µm. The characteristics of the two-phase flow were calculated through pore network modeling. The studies were conducted on 20 sub-volumes, which were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The results demonstrate that the relationship between connected total porosity is described well by the parabolic equation ϕ con = aϕ 2 + bϕ + c both before and after rock dissolution, giving high correlation coefficients R 2 ≈ 0.96 − 0.99. The percolation threshold porosity values found in this article align well with those reported in [31], and are approximately three times higher than the values for sandstones. It has been shown that, as a result of rock dissolution, the connectivity between pores increases for heterogeneous samples, as evident from the decrease in the percolation threshold porosity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results demonstrate that the relationship between connected total porosity is described well by the parabolic equation ϕ con = aϕ 2 + bϕ + c both before and after rock dissolution, giving high correlation coefficients R 2 ≈ 0.96 − 0.99. The percolation threshold porosity values found in this article align well with those reported in [31], and are approximately three times higher than the values for sandstones. It has been shown that, as a result of rock dissolution, the connectivity between pores increases for heterogeneous samples, as evident from the decrease in the percolation threshold porosity.…”
Section: Discussionsupporting
confidence: 89%
“…The experimental procedure involved cleaning each sample from oil, bitumen, and water-soluble salts, saturating it with a 2% NaCl solution, and maintaining it for 12 h at a temperature of 20 • C and a pressure of 3 MPa (reservoir conditions) [31]. Then, each sample was scanned using an X-ray microcomputed tomography General Electric V|tome|X S240 (Baker Hughes, Houston, TX, USA) at a resolution of about 18 µm before injecting HCl solution.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation